Community structure of the odonatofauna of an important Maghrebian watershed: the Seybouse (Northeast Algeria). Issue 4 (2nd October 2018) - Razkallah, Zahra; Houhamdi, Moussa
ABSTRACT: Odonata of the Maghreb have been shown to be particularly diverse and rich in endemic species. Although studies have peaked during the last decade, especially in the Seybouse watershed (Northeast Algeria), a few have used larvae to assess the community structure and ecology of odonates. Here, we present a larva-based investigation of the odonate of the Seybouse watershed conducted during 2015–2016 in a dozen of sites using community ecology quantitative approaches and multivariate analysis to determine the checklist, species richness, abundance, and environmental characteristics of communities. We found 17 species (7 zygopterans and 10 anisopterans), of which Calopteryx exul, Coenagrion mercuriale, Gomphus lucasii were locally and/or globally of conservation concern. There was a strong correlation between the frequency occurrence (distribution) and abundance, meaning that the cosmopolitan species were also the most abundant in the community. The multivariate analysis showed that the communities were structured by substrate type and abiotic factors such as conductivity, dissolved oxygen, and water flow. Our study also confirms the extinction of some populations of the endangered endemic C. exul, and thus rings the alarm for an urgent conservation plan that should manage the extensive water pumping and pollution in the region.